Nursing diagnosis in urgency and emergency (Research, Society and Development, 2021)
This article reports on the nursing diagnosis in urgency and emergency, being of extreme importance the hospital care taking into account all the momentary conditions related to the general state of the patient, the nursing professional performs his activity with agility and competence in the first visit. The research aims to report the role of the health professional and its importance in urgent and emergency diagnoses and in hospital care and highlight the priority of the developments of diagnoses collected by urgent and emergency professionals and help emergency room professionals to have a greater agility for patient care. This article adopts as a methodology the resources of bibliographic review, on the aspect of historical themes, employs on the study of references based on indirect documentation, with research of scientific articles, documentary research and bibliographic research, carried out in four stages, identification of the problem, literature search, data evaluation and analysis, and finally the synthesis of the bibliographic review. As results and Discussion this study acts on the importance of nursing diagnosis in urgency and emergency, being considered a great challenge, because every day this area of health there is overcrowding, so to maintain the quality of care is very complicated. Concluding about the importance of diagnoses and the relevance of data collection by health professionals, we can help to save many lives that would be lost due to the lack of diagnoses not collected during the service.